Candida glabrata susceptibility to antifungals and phagocytosis is modulated by acetate - Mota, Sandra; Alves, Rosana; Carneiro, Catarina; Silva, Sónia; Brown, Alistair J.; Istel, Fabian; Kuchler, Karl; Sampaio, Paula; Casal, Margarida; Henriques, Mariana; Paiva, Sandra (Frontiers in Microbiology, 2015)
Candida glabrata is considered a major opportunistic fungal pathogen of humans. The capacity of this yeast species to cause infections is dependent on the ability to grow within the human host environment and to assimilate the carbon sources available. Previous studies have suggested that C. albicans can encounter glucose-poor microenvironments during infection and that the ability to use alternative non-fermentable carbon sources, such as carboxylic acids, contributes to the virulence of this fungus. Transcriptional studies on C. glabrata cells identified a similar response, upon nutrient deprivation. In this work, we aimed at analysing biofilm formation, antifungal drug resistance and phagocytosis of C. glabrata cells grown in the presence of acetic acid as an alternative carbon source. C. glabrata planktonic cells grown in media containing acetic acid were more susceptible to fluconazole and were better phagocytosed and killed by macrophages than when compared to media lacking acetic acid. Growth in acetic acid also affected the ability of C. glabrata to form biofilms. The genes ADY2a, ADY2b, FPS1, FPS2 and ATO3, encoding putative carboxylate transporters, were upregulated in C. glabrata planktonic and biofilm cells in the presence of acetic acid. Phagocytosis assays with fps1 and ady2a mutant strains suggested a potential role of FPS1 and ADY2a in the phagocytosis process. These results highlight how acidic pH niches, associated with the presence of acetic acid, can impact in the treatment of C. glabrata infections, in particular in vaginal candidiasis.